The Level of Economic Activity / Economic Processes - Eggers Melvin A; Tussing Dale A (Holt, Rinehart And Winston, 1965)
Preface, The Study of Economics, The Cast of Characters, Services and Products and Production Groups, A First Look at Macroeconomic Relationships, Saving and Investment and Capital, Aggregate Income: Measuring Economic Activity, The Operations of Finance, The Institutions of Finance, Commercial Banks and Money, Control of the Money Supply, Changes in the Level of Economic Activity, Macroeconomic Relationships in Perspective, The Role of Government in the Level of Economic Activity, Issues of Fiscal Policy, The Financial System and the Level of Economic Activity, The Level of Prices, Policy Against Inflation, Economic Growth: The Aggregate View, Index.